2005
DOI: 10.1073/pnas.0406904102
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of human papillomavirus in cervical, head/neck, and schistosomiasis-associated bladder malignancies

Abstract: We assayed for the presence of human papilloma virus (HPV) DNA in serum and͞or peripheral blood fraction (PBF) of individuals with cervical, head͞neck, or bladder cancer due to schistosomiasis. Using mass spectroscopy coupled with competitive PCR, HPV DNA was detected at the individual molecule level by using ''Mass-ARRAY'' assays. The resultant sensitivity was superior to real-time fluorescent PCR-based assays, while specificity was maintained. Our principal findings were: (i) Virtually all tested cervical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 29 publications
1
52
1
Order By: Relevance
“…Slides were subsequently hybridized with a biotinylated HPV16 type -specific probe (DAKO) and, in selected cases, with a wide-spectrum HPV probe -specific for subtypes 6,11,18,31,33,35,45, 51, and 52.…”
mentioning
confidence: 99%
“…Slides were subsequently hybridized with a biotinylated HPV16 type -specific probe (DAKO) and, in selected cases, with a wide-spectrum HPV probe -specific for subtypes 6,11,18,31,33,35,45, 51, and 52.…”
mentioning
confidence: 99%
“…The use of different techniques and the type of tissue (frozen vs paraffin-embedded) does not fully account for the variability in detection rates. High prevalence of HPV has been shown not only in studies relying solely on PCR, 39,45 but also in studies where PCR was combined with Southern blot, 9,46 dot blot hybridization, 47 or in situ hybridization. 48,49 Other studies using the same methods yielded much lower rates of detection.…”
Section: Discussionmentioning
confidence: 99%
“…1 HPV is a small circular double-stranded DNA virus with more than 100 different types described to date. 2 The potential of the virus to cause malignant or benign lesions dictates its classification into low-risk (6,11,40,42, and so on) or high-risk (16,18,31,33,45,51, and so on) types. The prototypical model for carcinogenesis is squamous cell carcinoma of the uterine cervix, in which nearly all such carcinomas are associated with HPV infection.…”
mentioning
confidence: 99%
“…Similar was the opinion by the researchers from the Netherlands who carried out study of BC specimens from 107 patients and found DNA of various HPV types in ~ 15 %; HR-HPV DNA was detected in ~ 8 % (Moonen et al, 2007). Percentage of HR-HPV DNA-positive specimens increased with progression of clinical stage of BC (Ta, T1 and T2-T4), making 0, 12.5 and 18.2 % respectively Group of investigators from Egypt and USA presented data on HPV-positivity of 27 Schistosoma-associated BC cases (Yang et al, 2005). All of them harboured HPV16.…”
Section: The Recent Data Warn Against Hpv Underestimation As a Risk Fmentioning
confidence: 99%
“…Several researchers have published recently some data proving topicality of the HPV problem in BC aetiology (Barghi et al, 2005;Yang et al, 2005;Helal Tel et al, 2006;Moonen et al, 2007;Badawi et al, 2008). Thus ~ 36 % of transitional-cell BC specimens from Iran (21 out of 59 studied) harboured HPV DNA (Barghi et al, 2005).…”
Section: The Recent Data Warn Against Hpv Underestimation As a Risk Fmentioning
confidence: 99%